Relatório de Estágio Profissional "SER PROFESSORA DE EDUCAÇÃO FÍSICA: DO SONHO À REALIDADE" - Catarina Simões Martins (2019)
This report was prepared within the scope of the school placement, integratedin the second year of the Second Cycle in Teaching Physical Education in Basicand Secondary Education at the Faculty of Sport of the University of Porto. Theshool placemnet include two components, the supervised teaching practice andthe practicum report. The school placement was carried out in a cooperatingschool during a full school year, under the supervision of a cooperating teacher(of the school) and a supercisor (of the faculty), in a group of two preservicetecahers. The content of this document is the result of a first-person report of apreservice teacher about the school year. The document report the experiencesand activities carried out in the practicum context, which have often confrontedtheory and practice, referring to the need to reflect on the taken decisions.Throughout this school year I had the opportunity to prepare and teach threeclasses and assume the role of coach at the Sports School team, in Swimming.I participated at the Department meetings and Physical Education Groupmeetings, as well as in the meetings of the resident and shared classes. Inaddition, I established contacts with the Director of my resident class. Of all theopportunities I had during this year, the greatest and most valuable learningcame from the process experienced with the resident classe and the dailycoexistence with the other preservice teacher. It was also carried out a ActionresearchStudy, whose objective was to realize the potentialities of theimplementation of the evaluation principles assessment for learning for thestudents' learning. The results indicated that this methodology is excellent forthe teaching of all the sport whithi Physical Education classes, because whencentering the process on the students, a very positive classroom environment isbuilt up and learning is potentiated. In personal terms it was a year full oflearning and the realization of the dream to be a teacher.